Modern issues of pedagogy and psychology: theoretical and methodological approaches and practical research results - Gadzaova L. P., Makambaeva Y. Z., Murzaeva B. T., Satyvaldiev A. S., Shemiakina S. A., Sakharchuk E. I., Anikin V. M., Kupovykh G. V., Ryspaeva C. K., Akhunzhanova M. K., Maslennikova S. F., Medvedeva A. A., Temirkanova T. E., Doroschuk E. S., Zaritskaia V. V., Kozlova M. A., Kozlov A. V., Sabodina E. P., Kugai A. I., Kugai A. I., Bashkireva T. V., Bashkireva A. V., Shatokhina L. V., Smykovskaia T. K., Sergeev N. K., Korotkov A. M., Korepanova M. V., Rodionova I. V., Shapirova R. R., Akhtarieva R. F., Khotuliova O. V., Egorova G. V., Barashkina S. B., Zaluzhnaia M. V., Kostenko E. G., Kugai A. I., Isakova T. I., Zanin D. S. (Modern issues of pedagogy and psychology: theoretical and methodological approaches and practical research results, 2025)
the chapter presents a practical development of the situational role-playing method used in the course of teaching the discipline "Life safety" at a medical university. The goals and objectives of the lesson are considered, the competencies formed during the lesson are described, as well as the work plan.
Keywords: инклюзивное образование; медицина; inclusive education; medicine; интерактивные формы обучения; ситуационно-ролевая игра; interactive forms of education; situational role-playing